2008
DOI: 10.1091/mbc.e07-08-0749
|View full text |Cite
|
Sign up to set email alerts
|

Intraflagellar Transport and Functional Analysis of Genes Required for Flagellum Formation in Trypanosomes

Abstract: Intraflagellar transport (IFT) is the bidirectional movement of protein complexes required for cilia and flagella formation. We investigated IFT by analyzing nine conventional IFT genes and five novel putative IFT genes (PIFT) in Trypanosoma brucei that maintain its existing flagellum while assembling a new flagellum. Immunostaining against IFT172 or expression of tagged IFT20 or green fluorescent protein GFP::IFT52 revealed the presence of IFT proteins along the axoneme and at the basal body and probasal body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
250
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(281 citation statements)
references
References 70 publications
(133 reference statements)
26
250
0
2
Order By: Relevance
“…Instead, an axonemeless membrane sleeve extended alongside the cell body from TZ stubs (Fig. 6 C and D), similar to that observed in anterograde IFT mutants (40,41).…”
Section: Tz and Ciliary Subdomains Defined By Protein Localization Usingsupporting
confidence: 76%
“…Instead, an axonemeless membrane sleeve extended alongside the cell body from TZ stubs (Fig. 6 C and D), similar to that observed in anterograde IFT mutants (40,41).…”
Section: Tz and Ciliary Subdomains Defined By Protein Localization Usingsupporting
confidence: 76%
“…Although IFT38 was not identified in the pioneering characterizations of the IFT‐B complex (Piperno & Mead, 1997; Cole et al , 1998), several lines of evidence suggest that IFT38 is a bona fide IFT‐B complex protein. IFT38 localizes to the cilium and is required for ciliogenesis in a wide range of organisms, and mutations in IFT38 cause cystic kidneys in zebrafish and result in a loss of hedgehog signaling and embryonic lethality in mice (Sun et al , 2004; Stolc et al , 2005; Absalon et al , 2008). Furthermore, IFT38 was shown to undergo IFT in C. elegans (Ou et al , 2005) and co‐precipitated along with other IFT‐B proteins from zebrafish cell lysates using TAP‐IFT54 as a bait (Omori et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A single flagellum membrane-specific protein, the ESAG4 adenylate cyclase, has been identified in T. brucei (Paindavoine et al, 1992), and a calcium-binding flagellar membrane protein has been characterized in T. cruzi (Engman et al, 1989;Buchanan et al, 2005). In the flagellar matrix, several components of the intraflagellar transport pathway (IFT20, IFT52, IFT172) have recently been shown to exhibit both a soluble flagellar pool and a detergent-insoluble basal body-associated pool (Absalon et al, 2007a), but no other soluble flagellar proteins have been identified. Thus we have very little knowledge of the proteins that make up the matrix or membrane.…”
Section: Flagellar Membrane and Matrixmentioning
confidence: 99%
“…The DHC1b dynein then returns IFT particles to the base of the flagellum to reload with additional cargo (Pazour et al, 1999;Porter et al, 1999). Several conserved IFT components have now been identified and shown to function in T. brucei Davidge et al, 2006;Absalon et al, 2007a) and transport of an IFT52-GFP chimera has been directly visualized in live cells (Absalon et al, 2007a). Notably, since the trypanosome flagellum exhibits many unique structural features, these parasites may also possess unique IFT machinery.…”
Section: Flagellum Biogenesismentioning
confidence: 99%